2016
DOI: 10.14740/gr715w
|View full text |Cite
|
Sign up to set email alerts
|

No Need of Fascia Closure to Reduce Trocar Site Hernia Rate in Laparoscopic Surgery: A Prospective Study of 200 Non-Obese Patients

Abstract: BackgroundLaparoscopy is widely practiced and offers realistic benefits over conventional surgery. Port closure is important after a laparoscopic procedure to prevent port site incisional hernia. Larger port size and increasing numbers of ports needed to perform more complex laparoscopic procedures are likely to increase the incidence of port site hernias (PSHs). PSHs tend to develop more frequently at umbilical and midline port sites due to the thinness of the umbilical skin and weaknesses in the linea alba. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Moreover, in present study improvised techniques to avoid port-site hernia such as use of standard closure (via skin wound), direct visualization closure method and use of suture passer needle were used which itself help in reducing the port site hernia rate. [28] Similar to our study, Singal et al [28] in their study also showed that use of improvised techniques can minimize the incidence of port-site incisional hernia to 0%.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, in present study improvised techniques to avoid port-site hernia such as use of standard closure (via skin wound), direct visualization closure method and use of suture passer needle were used which itself help in reducing the port site hernia rate. [28] Similar to our study, Singal et al [28] in their study also showed that use of improvised techniques can minimize the incidence of port-site incisional hernia to 0%.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that the use of suture for ligation is cost-effective and economical for ligation. q DISCUSSIONS L aparoscopy is widely practiced and it offers realistic benefits over conventional surgery (5). It was first performed by Carl Langenbuch in 1882, and in 1983 Kurt Semm used an automatic insufflation device for assessing intra-abdominal pressures (6).…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference in the presence of complications in the two groups. 12 As more surgical expertise is needed with single incision laparoscopic procedures, port site complications and wound complication risk cannot be studied properly. The risk of complications decreases as the experience of the surgeon increases.…”
Section: Discussionmentioning
confidence: 99%